KUALITAS PAPAN KOMPOSIT DARI SABUT KELAPA DAN LIMBAH PLASTIK BERLAPIS BAMBU DENGAN VARIASI KERAPATAN DAN LAMA PERENDAMAN NaOH - Anggrainie, Ovythia; Setyawati, Dina; haida, Nur (JURNAL HUTAN LESTARI, 2013)
The aim of this research is to investigate the varios of NaOH immersion treatments and the density of optimal and the best composite board mechanic and physical. Factor of research were the varios of NaOH immersion treatments (control, 2 hour, 4 hour, 6 hour) and varios density ( 0,6 gr/cm3 and 0,7 gr/cm3). The composite board were mixed manually with weight both of polyprophylenes plastic and coir fibres to all of composite board comparison 50 : 50 after were reduced weight of bamboo slats. The composite boards were made with dimension 30 cm 30 cm x 1 cm, where the bamboos were made become face and back of board then both plastic and coir fibres were core board. The recycle polyprophylenes plastic distributed were devided by three parts, those were face layer 15 %, core layer 70 %, and back layer 15 % of plastics weight. The pressure was done with hot press temperature 180 oC for 20 minute with pessure 25 kg/cm. Results of research have showed that physical and mechanical properties oof composite board were increased with the addition of density composite board and reduced of NaOH immersion treatments. Composite board without NaOHs immersion with density 0,7 gr/cm3 is the best and optimum result of composite board. Key words : composite board, coconut fiber, recycled polyprophylene, bamboo layers